Identifying molecular pathways and candidate genes associated with knob traits by transcriptome analysis in the goose (Anser cygnoides) - Wangyang Ji (Nature Portfolio, 2021)
Abstract Anser cygnoides has a spherical crest on the beak roof, which is described as knob. However, the mechanisms affecting knob morphology are unclear. Here, we investigated the phenotypic characteristics and molecular basis of knob-size differences in Yangzhou geese. Anatomically, the knob was identified as frontal hump in the frontal area of the skull, rather than hump of upper beak. Although the frontal hump length, and height varied greatly in geese with different knob phenotypes, little was changed in the width. Histologically, knob skin in large-size knobs geese have a greater length in the stratum corneum, stratum spinosum, and stratum reticular than that in small-size knobs geese. Moveover, the 415 differentially expressed genes were found between the large knobs and small ones through transcriptome profiling. In addition, GO enrichment and KEGG pathway analysis revealed 455 significant GO terms and 210 KEGG pathways were enriched, respectively. Among these, TGF-β signaling and thyroid hormone synthesis-signaling pathways were identified to determine knob-size phenotype. Furthermore, BMP5, DCN, TSHR and ADCY3 were recognized to involve in the growth and development of knob. Our data provide comprehensive molecular determinants of knob size phenotype, which can potentially promote the genetic improvement of goose knobs.